Theoretical conceptualization of a teacher development program in selected Malaysian Teacher Education Institutes - Mohamed, Ismail (2015)
Malaysian Teacher Education Institutes administer a teacher development program called Teacher Character Development Program (Program Bina Insan Guru, BIG) in order to develop its student teachers’ character that complies with the Teacher Professional Values Practices standard. A qualitative case study research was conducted to explicate the program’s concept on developing a teacher character through the program activities. 13 stakeholders consisted of 4 policy makers, 7 implementers and 2 program participants, were selected using purposive and snowball sampling for interviews. In addition document analysis of 10 program documents and observation on 2 program implementations were conducted to triangulate research data. The finding showed that the program’s stakeholders have an implicit concept about the program that was not explicitly written in the BIG program’s documents. The program was not faithfully implemented based on the program’s module or the implicit concept because of financial problem and lack of understanding of the program’s concept among the implementers. Reflection is the most important activity in this program but the mentors do not seem to realize their role in this activity. If the implementers are not able to understand this implicit program concept, they might not be able to modify the program planning without distorting its effectiveness in developing student teachers’ character. A new conceptual framework was developed based on stakeholders’ implicit conceptualization, document analysis and literature reviews of several social science theories. This new conceptual framework can be used to guide the implementers’ training, continuous improvement of the program, program evaluation, and further research on program development and character education. The role of mentors and their functions in this program have been described in this research to guide the policy makers in order to improve the program effectiveness.